2018
DOI: 10.1371/journal.pbio.2006092
|View full text |Cite
|
Sign up to set email alerts
|

Refined RIP-seq protocol for epitranscriptome analysis with low input materials

Abstract: N6-Methyladenosine (m6A) accounts for approximately 0.2% to 0.6% of all adenosine in mammalian mRNA, representing the most abundant internal mRNA modifications. m6A RNA immunoprecipitation followed by high-throughput sequencing (MeRIP-seq) is a powerful technique to map the m6A location transcriptome-wide. However, this method typically requires 300 μg of total RNA, which limits its application to patient tumors. In this study, we present a refined m6A MeRIP-seq protocol and analysis pipeline that can be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 55 publications
4
121
0
Order By: Relevance
“…Our experience with eCLIP suggests that the input amounts we describe for our protocol could be reduced while still producing quality results, although we have not yet systematically tested the range of adequate RNA input. Consistent with recent reports (Zeng et al 2018), however, we find that the number of unique m 6 A sites identified does increase with higher amounts of input RNA. Therefore, in addition to ensuring accurate quantification of starting material via the methods outlined in our protocol, we also highly encourage the use of multiple replicates when starting RNA material is limited to gain confidence in the identified m 6 A residues.…”
Section: Discussionsupporting
confidence: 92%
“…Our experience with eCLIP suggests that the input amounts we describe for our protocol could be reduced while still producing quality results, although we have not yet systematically tested the range of adequate RNA input. Consistent with recent reports (Zeng et al 2018), however, we find that the number of unique m 6 A sites identified does increase with higher amounts of input RNA. Therefore, in addition to ensuring accurate quantification of starting material via the methods outlined in our protocol, we also highly encourage the use of multiple replicates when starting RNA material is limited to gain confidence in the identified m 6 A residues.…”
Section: Discussionsupporting
confidence: 92%
“…To investigate the distribution and dynamics of the m 6 A and m 6 Am among different tissues, transcriptome-wide m 6 A and m 6 Am mapping was performed. Due to the limited amount and partial degraded nature of human tissue RNA samples, we adopted a recently published refined RIP-seq protocol for low-input materials with several modifications (Zeng et al, 2018). It is worth mentioning that instead of random priming, a template-switching reaction at 5’ end of RNA template was used during library construction so that the 5’ end sequence information of RNA was preserved.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure was performed according to the recently described “Refined RIP-seq” with several modifications(Zeng et al, 2018). 3 μg total RNA was fragmented into ∼130-nucleotide-long fragments by magnesium RNA fragmentation buffer (NEB, E6150S).…”
Section: Star Methodsmentioning
confidence: 99%
“…Typically these approaches require micrograms of polyadenylated starting material (Dominissini et al, 2012;Ke et al, 2015;Linder et al, 2015;Meyer et al, 2012;Schwartz et al, 2013) , which prohibited interrogation of m6A levels in purified populations of cells, clinical settings, or within specific subcellular compartments. While optimized protocols substantially reduced the starting amounts of mRNA (Merkurjev et al, 2018;Zeng et al, 2018) , no protocol exists providing single nucleotide resolution mapping from limited starting mRNA material.…”
Section: Introductionmentioning
confidence: 99%